1990
DOI: 10.1086/269227
|View full text |Cite
|
Sign up to set email alerts
|

Context Effects for Census Measures of Race and Hispanic Origin

Abstract: This paper reports on the results of a split-ballot experiment conducted in 1987 to test alternative versions of the decennial census long form. Two forms were randomly assigned and self-administered in group sessions involving a total of 515 respondents. The order of race and Hispanic origin items was experimentally manipulated. The standard long form asks race, then Hispanic origin. The experimental form reversed the order of the items in order to reduce perceived redundancy, and to create a more restricted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
30
0

Year Published

1997
1997
2012
2012

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 9 publications
1
30
0
Order By: Relevance
“…Positioning of questions is explicitly used to increase the numbers completing the 'right' box (Bates et al, 2006, Martin et al, 1990. In the UK 2011 census, the proposed placing of a national identity question prior to the ethnic group question is designed to allow all those who wish to assert their Britishness to have an initial opportunity to do so, with the intended result that fewer minorities will 'incorrectly' subsequently select the British sub-option of 'white' or use the write-in sections to define themselves as British.…”
Section: Measurement Issuesmentioning
confidence: 99%
“…Positioning of questions is explicitly used to increase the numbers completing the 'right' box (Bates et al, 2006, Martin et al, 1990. In the UK 2011 census, the proposed placing of a national identity question prior to the ethnic group question is designed to allow all those who wish to assert their Britishness to have an initial opportunity to do so, with the intended result that fewer minorities will 'incorrectly' subsequently select the British sub-option of 'white' or use the write-in sections to define themselves as British.…”
Section: Measurement Issuesmentioning
confidence: 99%
“…18 In the 1940 census, and for 3 decades thereafter, Mexicans and others of "Latin descent" were generally categorized as "White." 73 When, in 1980, both the short and long forms of the census included Hispanic ethnicity, Latinos were still bifurcated by color. If in recent decades the census has recognized the need to find new distinctions among racial groups (Pacific Islanders and Hawaiian natives were distinguished from Asians in the 2000 census), the results are still crude.…”
Section: Implications For a New Population Taxonomymentioning
confidence: 99%
“…[42][43][44][45][46] An experiment to test the effects of the ordering of ethnicity and race questions on Hispanics' reporting of "other race" found that the percentage of Hispanics reporting "other race" decreased only for Hispanics born in the United States, not for Hispanic immigrants. 47 The authors of the report argued that Hispanics'reporting of "other race" is not an error but a real perception of respondents who do not see themselves as "White" or "Black." 47 These findings suggest that cultural adaptation, notions of space, and changes in the perception of oneself within the United States are a dynamic process for Hispanics.…”
Section: Measurement Of a Dynamic Processmentioning
confidence: 99%
“…47 The authors of the report argued that Hispanics'reporting of "other race" is not an error but a real perception of respondents who do not see themselves as "White" or "Black." 47 These findings suggest that cultural adaptation, notions of space, and changes in the perception of oneself within the United States are a dynamic process for Hispanics.…”
Section: Measurement Of a Dynamic Processmentioning
confidence: 99%